The effect of source thickness and density on Ge (Li) detection efficiency / Ahmad Saat - Saat, Ahmad (Universiti Teknologi MARA, Pahang, 1993)
A study was carried out on the effect of different source thickness (0.5 cm, 0.75 cm, 1.0 cm and 1.25 cm) on a Ge(Li) detector's relative efficiency. The effect of sample density was also studied. It was found that for a particular energy of a gamma photon. the relative efficiency increases as the thickness decreases. For the range of mass (hence, density) studied it was found that the effect on the relative efficiency is very little.